Global health crises are also information crises: A call to action. (13th March 2020) - Xie, Bo; He, Daqing; Mercer, Tim; Wang, Youfa; Wu, Dan; Fleischmann, Kenneth R.; Zhang, Yan; Yoder, Linda H.; Stephens, Keri K.; Mackert, Michael; Lee, Min Kyung
Abstract: In this opinion paper, we argue that global health crises are also information crises. Using as an example the coronavirus disease 2019 (COVID‐19) epidemic, we (a) examine challenges associated with what we term "global information crises"; (b) recommend changes needed for the field of information science to play a leading role in such crises; and (c) propose actionable items for short‐ and long‐term research, education, and practice in information science.